2019
DOI: 10.1126/sciadv.aav9946
|View full text |Cite
|
Sign up to set email alerts
|

Sortilin gates neurotensin and BDNF signaling to control peripheral neuropathic pain

Abstract: Neuropathic pain is a major incurable clinical problem resulting from peripheral nerve trauma or disease. A central mechanism is the reduced expression of the potassium chloride cotransporter 2 (KCC2) in dorsal horn neurons induced by brain-derived neurotrophic factor (BDNF), causing neuronal disinhibition within spinal nociceptive pathways. Here, we demonstrate how neurotensin receptor 2 (NTSR2) signaling impairs BDNF-induced spinal KCC2 down-regulation, showing how these two pathways converge to control the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 46 publications
1
50
0
Order By: Relevance
“…Indeed, macrophage‐neuron interactions have been suggested to be crucial for peripheral sensitization and neuropathic pain (Marchand, Perretti, & McMahon, ; Moalem & Tracey, ; Santa‐Cecília et al, ; Vega‐Avelaira et al, ; Zigmond & Echevarria, ). The timing of this migration is also suggestive: Mice have been shown to develop mechanical allodynia during the first 2–3 days after nerve injury (Richner et al, ; Richner, Bjerrum, Nykjaer, & Vaegter, ), which coincides with the formation of the “ring‐like” structures we report here. We find here that the gene ccl2 encoding the chemokine monocyte chemoattractant protein 1 (MCP1) is upregulated in SGC on Day 3.…”
Section: Discussionsupporting
confidence: 74%
“…Indeed, macrophage‐neuron interactions have been suggested to be crucial for peripheral sensitization and neuropathic pain (Marchand, Perretti, & McMahon, ; Moalem & Tracey, ; Santa‐Cecília et al, ; Vega‐Avelaira et al, ; Zigmond & Echevarria, ). The timing of this migration is also suggestive: Mice have been shown to develop mechanical allodynia during the first 2–3 days after nerve injury (Richner et al, ; Richner, Bjerrum, Nykjaer, & Vaegter, ), which coincides with the formation of the “ring‐like” structures we report here. We find here that the gene ccl2 encoding the chemokine monocyte chemoattractant protein 1 (MCP1) is upregulated in SGC on Day 3.…”
Section: Discussionsupporting
confidence: 74%
“…It is interesting to note that TrkB signaling appears common to both the loss of KCC2 48,50,51,53,54 as well as to the synaptic scaling at GABA A synapses and subunit switch, yet the changes in GABA A R were not secondary to loss of KCC2. We also found that the GABA A R plasticity was Ca 2+ dependent.…”
Section: Discussionmentioning
confidence: 99%
“…The switch in GABA A R subunit composition is BDNFdependent. After PNI, activation of spinal microglial P2X4Rs evokes the release of BDNF 48,49 which is known to down-regulate neuronal KCC2 expression [50][51][52][53][54] . To test whether BDNF was also involved in the GABA A R subunit switch, we incubated slices from control animals for 3 h with BDNF ( Fig.…”
Section: Decrease In Number Of Inhibitory Synapses After Nerve Injurymentioning
confidence: 99%
“…Neuropathic pain is characterized as a hypersensitive response to noxious and innocuous stimuli that results from primary injury or dysfunction of the somatosensory nervous system; it can persist for months to years, even after the primary tissue damage has healed [1]. Neuropathic pain remains as a chronic debilitating condition that affects the quality of life and reduces individual productivity; it is estimated to affect up to 10% of the population [2,3]. The etiology of neuropathic pain is complex and includes diabetic neuropathy, spinal cord injury, post-herpetic neuralgia, demyelinating disease, and cancer.…”
Section: Introductionmentioning
confidence: 99%